2016
DOI: 10.1542/peds.2015-0812
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity-Related Asthma: The Role of Metabolic Dysregulation

Abstract: The burden of obesity-related asthma among children, particularly among ethnic minorities, necessitates an improved understanding of the underlying disease mechanisms. Although obesity is an independent risk factor for asthma, not all obese children develop asthma. Several recent studies have elucidated mechanisms, including the role of diet, sedentary lifestyle, mechanical fat load, and adiposity-mediated inflammation that may underlie the obese asthma pathophysiology. Here, we review these recent studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 155 publications
(111 reference statements)
3
65
0
4
Order By: Relevance
“…This is in line with a meta‐analysis on the relationship between overweight and incident asthma in childhood of Chen et al, which showed a significantly stronger relationship between BMI z ‐score and asthma in boys, compared to girls . This gender different association between BMI and asthma we observed was also disclosed in the review of Vijayakanthi et al…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with a meta‐analysis on the relationship between overweight and incident asthma in childhood of Chen et al, which showed a significantly stronger relationship between BMI z ‐score and asthma in boys, compared to girls . This gender different association between BMI and asthma we observed was also disclosed in the review of Vijayakanthi et al…”
Section: Discussionsupporting
confidence: 92%
“…[46][47][48][49][50] The practical consequence is that OSA should be excluded in DA and STRA (testing depending on the level of suspicion), and treated if present on its merits. Whether treatment of OSA will be beneficial to asthma control will likely vary between individual patients.…”
Section: Obesitymentioning
confidence: 99%
“…For example, obesity has been implicated in OSA even after adenotonsillectomy, 6 as well as in the development of asthma. 7 A bidirectional association between asthma and OSA has also been described, thought in part to be secondary to increased vagal tone and inflammation leading to increased airway resistance. 8 Although there is extensive insight into these individual relationships, little is known about how all three comorbid conditions may interact.…”
Section: Introductionmentioning
confidence: 99%